Keefektifan Permainan Susun Kata Untuk Penguasaan Partikel Bahasa Jepang Pada Siswa Kelas XI MAN 2 Pekanbaru - ,, Winda; Nimashita, Hana; Utami, Mutiara (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
AbstractThe use of Japanese particles remains a challenge for students, as they oftenstruggle to distinguish particle functions, determine their correct positions withinsentences, and maintain focus during learning activities. Therefore, a wordarrangement game was implemented in the learning process. This study aims toexamine the effectiveness of the word arrangement game in improving students’mastery of basic Japanese particles. The research employed a quantitativeapproach with a quasi-experimental pretest–posttest control group designinvolving 62 eleventh-grade students of MAN 2 Pekanbaru, divided intoexperimental and control classes. The research instruments consisted of pretestand posttest items totaling 30 questions, analyzed using the Shapiro–Wilknormality test, homogeneity test, independent t-test, and Mann–Whitney U test.The results showed that the experimental class obtained a higher posttest meanscore (72.19) than the control class (56.77), with a significance value of 0.001(<0.05). Thus, it can be concluded that the word arrangement game is effective inenhancing students’ mastery of Japanese particles, although their overall achievement remains in the low category.The particles most frequently used in students’ constructed sentences were wa, o, no, and de.Keywords:Japanese particles, wordarrangement game, languagelearning.